2007
DOI: 10.1016/j.juro.2007.05.129
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Clinically Significant Castration Levels in Patients With Prostate Cancer Receiving Continuous Androgen Deprivation Therapy

Abstract: In the current report the lowest testosterone castration level with clinical relevance in medically castrated patients with prostate cancer was 32 ng/dl. Breakthrough increases greater than this threshold predicted a lower survival free of androgen independent progression. Maximal androgen blockade might benefit medically castrated cases of prostate cancer with breakthrough increases of more than 50 ng/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
206
1
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(226 citation statements)
references
References 14 publications
4
206
1
14
Order By: Relevance
“…24 Several studies have shown a correlation between adequate testosterone suppression and freedom from progression to castrate-resistant disease. 13,28 Among 73 patients with non-metastatic prostate cancer receiving three-month depots of LHRH agonist, 41 patients had progressed to castrate-resistant prostate cancer (CRPC) after a median followup of 51 months. 13 Testosterone breakthroughs above 1.7 nmol/L and 1.1 nmol/L were found to be predictors of progression to CRPC.…”
Section: Clinical Significance Of Testosterone Suppressionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Several studies have shown a correlation between adequate testosterone suppression and freedom from progression to castrate-resistant disease. 13,28 Among 73 patients with non-metastatic prostate cancer receiving three-month depots of LHRH agonist, 41 patients had progressed to castrate-resistant prostate cancer (CRPC) after a median followup of 51 months. 13 Testosterone breakthroughs above 1.7 nmol/L and 1.1 nmol/L were found to be predictors of progression to CRPC.…”
Section: Clinical Significance Of Testosterone Suppressionmentioning
confidence: 99%
“…13,28 Among 73 patients with non-metastatic prostate cancer receiving three-month depots of LHRH agonist, 41 patients had progressed to castrate-resistant prostate cancer (CRPC) after a median followup of 51 months. 13 Testosterone breakthroughs above 1.7 nmol/L and 1.1 nmol/L were found to be predictors of progression to CRPC. Mean survival free of androgen-independent progression was 88 months in patients with testosterone breakthroughs above 1.1 nmol/L, compared with 137 months in those without breakthrough increases (p<0.03).…”
Section: Clinical Significance Of Testosterone Suppressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 6-month study, > 30% of patients receiving an LHRH agonist with or without bicalutamide recorded a testosterone breakthrough of 0.2 ng/ mL to 0.5 ng/mL, whereas 25% recorded breakthroughs of > 0.5 ng/mL. 53 It remains to be determined whether "mini" testosterone; surges adversely impact the outcomes of men with localized androgen-sensitive disease receiving short-term ADT.…”
Section: Lhrh Agonistsmentioning
confidence: 99%